“Strategies for Enhancing Production Performance through Modern Management Methodologies: An Applied Study in Libyan Industrial Enterprises” (Comprehensive Journal of Science, 2026)
Strategies for Enhancing Production Performance through Modern Management Methodologies: An Applied Study in Libyan Industrial EnterprisesThe Libyan industrial sector faces growing challenges related to low operational efficiency, rising production costs, and weak competitiveness in a volatile economic and administrative environment. This research aims to examine the impact of applying modern management methodologies in production management, including Lean Production, Continuous Improvement (Kaizen), Value Engineering, and Total Productive Maintenance (TPM), on improving industrial performance in Libya.The study employed a descriptive-analytical and applied methodology, using field data collected from two major Libyan water bottling plants — Al-Sultan and Al-Safia. Data were gathered through a structured questionnaire targeting engineers, technicians, and production supervisors, and analyzed using the SPSS statistical software.Findings revealed a strong positive correlation between the application of Value Engineering and production performance (r = 0.75 for Al-Sultan and r = 0.61 for Al-Safia), indicating that modern production methodologies effectively enhance operational efficiency, reduce costs, and improve product quality. However, the study also identified challenges related to limited training, weak managerial awareness, and the absence of a culture of continuous improvement.Based on these results, the research proposes a strategic model for improving production performance built upon five main dimensions: strategic, organizational, technical, human, and value-based. The model integrates Value Engineering as a core component to achieve an optimal balance between cost, quality, and productivity.The study concludes that sustainable improvement in Libyan industrial performance requires supportive leadership and a participatory organizational culture that fosters innovation.